Functional Imaging and Modeling of the Heart : 8th International Conference, FIMH 2015, Maastricht, The Netherlands, June 25-27, 2015. Proceedings - van Assen, Hans.; Bovendeerd, Peter; Delhaas, Tammo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Functional Imaging and Modeling of the Heart, held in Maastricht, The Netherlands, in June 2015. The 54 revised full papers were carefully reviewed and selected from 72 submissions. The focus of the papers is on following topics: function; imaging; models of mechanics; and models of electrophysiology.
Function -- Imaging -- Models of mechanics.- Models of electrophysiology.
Keywords: Computer vision; Computer simulation; Bioinformatics; Computer graphics; Cardiology; Radiology, Medical; Image Processing and Computer Vision; Simulation and Modeling; Computational Biology/Bioinformatics.; Computer Graphics; Cardiology; Imaging / Radiology